Women who watch and support English football in Zimbabwe: a transnational analysis of female fandoms - Chiweshe, Kudzai Manase; Choto, Tafadzwa (Taylor and Francis, 2022)
In this paper, we explore the lived experiences of women who watch and support English football teams in Zimbabwe. We utilized a qualitative research approach that included in-depth interviews and football ethnographies in spaces where English football is consumed such as bars, betting halls, upmarket clubs, restaurants, hotels, and sports clubs. The paper provides a nuanced analysis of how women become part of and participate in transnational forms of cultural consumption, in this case, English football. Other major themes outlined in the paper include how and where women consume English football, performance and practices of female fans. Firstly, from our observation and fieldwork experiences in Zimbabwe men make up most transnational fans. Secondly, the spaces where football is consumed especially public spaces are male dominated. The paper concludes that transnational fan identities are gendered in multiple ways.